THE SEISMIC CHARACTERISTICS OF NORTHERN PART OF KULONPROGO - Ruwantro, Bambang; Sumardi, Yosaphat; Darmawan, Denny (Jurnal Penelitian Saintek, 2017)
Microtremor signal measurements had been conducted in the northern part of Kulonprogro to obtain the seismic characteristics in the form of: the predominant frequency value, ampliï¬ cation factor, sediment thickness, seismic vulnerability index, the maximum ground vibration acceleration, and the ground shear strain value. The measurement was conducted at 18 points within geographical coordinates of 110.10° E-110.27° E and 7.64° S-7.80° S. The signals were analyzed using Horizontal to Vertical Spectral Ratio (HVSR) method. The results show that the predominant frequency value is in the range of 2.98-13.53 Hz; ampliï¬ cation factor is in the range of 1.6-10.1; sediment thickness is in the range of 5-60 m; seismic vulnerability index is in the range of 0.6 í— 10 -6-5.8 í— 10 -6 s /cm; maximum ground acceleration is in the range of 24-54 gal and ground shear strain value is in the range of 0.6 í— 10 -4 – 4.4 í— 10 -4.